Analisis Pengaruh Kualitas Pelayanan, Harga Dan Fasilitas Terhadap Kepuasan Konsumen Pada Pandawa Water World Solo Baru - Prastito, Agung, Lukman Hakim, S.E., M.Si (2015)
The purpose of this study is to investigate the influence of service quality on customer satisfaction at Pandawa Water World Solo Baru.Untuk investigate the influence of price on consumer satisfaction at Pandawa Water World in Solo Baru.Untuk investigate the effect of the facility to consumer satisfaction at Pandawa Water World New Solo. The sampling technique used was accidental sampling technique, which used a sample of 100 respondents, while the tools of analysis used multiple linear regression analysis, t test, F test and the coefficient of determination (R2). Based on the results of this research note coefficient of determination (R2) = 0.551 55.1 can be said that the variable quality of service (X1), price (X2) and facilities (X3) influence on consumer satisfaction, while the remaining 44.9% is due to the influence of variables others are not covered in this study. The test results obtained value F Fhitung 41.443 while Ftabel at 5% significance level was 2.76 turns F count larger than F table then Ho or the null hypothesis is rejected to conclude the variable quality of service (X1), price (X2) and facilities (X3 ) has significant influence jointly on customer satisfaction. Results of t test analysis of unknown variables of service quality has a significant influence positive and significant impact on customer satisfaction. Price variables have a significant influence positive and significant impact on customer satisfaction. Variable facilities have significant positive and significant influence on customer satisfaction.